PENGARUH DIMENSI STORE ATMOSPHERE TERHADAP MINAT BELI - Mohammad Barqi Tobroni (Universitas Ahmad Dahlan, 2022)
This study aims to determine the effect of store atmosphere on purchase intention. The store atmosphere is assessed based on several indicators which are cleanliness, music, aroma, temperature, lighting, layout, and the room's color. The sample of this study was customers of IKEA Indonesia. The data analysis used in this study includes validity test, reliability test, and hypothesis test. The results of this study indicate that the aroma, color of the room, and store layout have a positive influence on purchase intention. While the cleanliness, music, temperature, and lighting variables have a positive but no significant influence on purchase intention.